2020
DOI: 10.1177/1029864920951611
|View full text |Cite
|
Sign up to set email alerts
|

Fans of Violent Music: The Role of Passion in Positive and Negative Emotional Experience

Abstract: Extreme metal and rap music with violent themes are sometimes blamed for eliciting antisocial behaviours, but growing evidence suggests that music with violent themes can have positive emotional, cognitive, and social consequences for fans. We addressed this apparent paradox by comparing how fans of violent and non-violent music respond emotionally to music. We also characterised the psychosocial functions of music for fans of violent and non-violent music, and their passion for music. Fans of violent extreme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 69 publications
2
51
0
Order By: Relevance
“…Therefore, across all participants there was a positive association between depressive symptoms and fear responses to music, and perhaps not surprisingly, a tendency to use music as a means of distracting oneself from negative emotions somewhat decreased the strength of this relationship-an effect that requires investigation in future research. Olsen et al (2020) report that fans of violently themed music experience a significantly greater magnitude of negative emotions in response to their favorite music when compared to the experience of fans of classical music. The results of the present study show that this phenomenon is not due to fans of violently themed music exhibiting greater depressive symptoms than fans of nonviolently themed music.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, across all participants there was a positive association between depressive symptoms and fear responses to music, and perhaps not surprisingly, a tendency to use music as a means of distracting oneself from negative emotions somewhat decreased the strength of this relationship-an effect that requires investigation in future research. Olsen et al (2020) report that fans of violently themed music experience a significantly greater magnitude of negative emotions in response to their favorite music when compared to the experience of fans of classical music. The results of the present study show that this phenomenon is not due to fans of violently themed music exhibiting greater depressive symptoms than fans of nonviolently themed music.…”
Section: Discussionmentioning
confidence: 98%
“…The classical music was selected from Baroque, Classical, and Romantic eras spanning from 1600 to 1820. Extreme metal stimuli were excerpts from songs used in Thompson et al (2019) and Olsen et al (2020). Excerpts of violent rap music and classical music were excerpts from songs used by Olsen et al (2020).…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…A lot of heavy metal music is perceived as violent and aggressive, and is consistent with auditory threat signals (Ollivier et al 2019), so there has been a continual association between heavy metal and immoral or violent behavior, but that connection is largely unfounded. Rather, it has been found that heavy metal, including with violent themes, consistently has positive emotional, cognitive, and social consequences for fans (Messick 2020;Olsen et al 2020;Sharman and Dingle 2015;Leisuk 2010;McFerran et al 2015). It has also been shown that heavy metal music is used by people with some dis/abilities and mental health disorders to help manage their mood and symptoms (Messick, Aranda, and Day 2020;Gebhardt, Kunkel, and Goergi 2016;Gebhardt and von Georgi 2007).…”
Section: Mood and Symptom Maintenancementioning
confidence: 99%